Actividad con funcionarios de la UNED. (UNED, 2024)
Atrás de izquierda a derecha de primero Eddy Lizano Arias, Walter Vargas Ortega, Mario Sibaja Bustamante, Carlos Morgán Marín, Adelante de izquierda a derecha de primero Rogelio Cordero Carrillo, Edwin Chavarría Montero, de cuarto Alejandro Rojas Sanabria